Gambaran Perkembangan Sosioemosional pada Remaja Perempuan Penyintas Kekerasan Emosional di Panti Asuhan “X” di Ambarawa - S, Stefani Setiaputri; Kristinawati, Wahyuni (Universitas Batanghari Jambi, 2025)
This study aims to be able to know and provide an empirical picture related to the description of socioemotional development in adolescent girls who are survivors of emotional violence at Orphanage